Jumping the queue: An experiment on procedural preferences - Dold, Malte; Khadjavi, Menusch (Games and economic behavior, 2017)
We present a three-player queuing game to study procedural preferences in a laboratory experiment. Together with markets, queues and waiting lists are universal procedures for allocating goods and services. We designed our queuing game to disentangle motivations of outcome-oriented egoistic preferences, outcome-oriented distributional (inequality aversion) preferences and outcome-independent procedural preferences. In a series of treatments, we introduce a market element and allow two of the three players to bargain over a queue jump, thus violating the queuing procedure. A third player is able to engage in peer punishment to sanction queue jumping. We provide evidence that a simple model of procedural preferences is able to explain the behavior of a share of the subjects in our experiment.